KEHALALAN PRODUK MAKANAN DALAM UPAYA PERLINDUNGAN KONSUMEN (STUDY PADA IZZI BAKERY) - Siti Aisyah; Yeni fatur rohmah; Santi rahmawati (IZZI: Jurnal Ekonomi Islam, 2021)
As a large country with a majority Muslim population, it is certainly an irony that the consumption needs of the Indonesian people are not fully guaranteed to be halal, and no party can really ensure that raw materials or finished products are circulated and traded. guaranteed halal in the market. This study aims to study in depth about the halalness of food products in an effort to protect consumers of izzi bakery products in pp Al-mashduqiah benchmark kraksaan. This type of research uses qualitative methods. The definition of methodology as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. Data collection techniques used are observation, interviews, and data from documentation. The data analysis technique uses secondary data, namely interviews and direct observation. Based on interviews conducted at izzi bakery, it shows that halal food products in an effort to protect consumers have been implemented by employees at izzi. Based on the results of the study, it can be concluded that izzi bakery products have implemented standardization of halal products and the Consumer Protection Act in an effort to ensure the achievement of consumer protection.